Managing Education Reform: Lessons from the Korean Experience 1995-97 - Se-il Park (Korea Development Institute (KDI), 2000)
This book reviews the process of education reform implemented during the years 1995 to 1997. It examines such issues as what have been goals and objectives of education reform in Korea. How has reform been initiated and implemented? What have been major difficulties and hurdles? Has reform been successful? If yes, what are the major factors contributing to success? If not, why not? After examining reform process, the book tries to draw some lessons from the Korean experience for the better management of education reform. The author believes that the lessons from the Korean reform experience can aid in developing appropriate strategies for successful education reform both in future Korea and in other countries. There have been many studies on what to reform to achieve rapid economic and social development, but very little studies on how to reform. I hope that this book can contribute to the study of successful reform management.
Keywords: 330